2014
DOI: 10.1038/ncomms4320
|View full text |Cite
|
Sign up to set email alerts
|

Free-surface molecular command systems for photoalignment of liquid crystalline materials

Abstract: The orientation of liquid crystal molecules is very sensitive towards contacting surfaces, and this phenomenon is critical during the fabrication of liquid crystal display panels, as well as optical and memory devices. To date, research has focused on designing and modifying solid surfaces. Here we report an approach to control the orientation of liquid crystals from the free (air) surface side: a skin layer at the free surface was prepared using a non-photoresponsive liquid crystalline polymer film by surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
159
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(163 citation statements)
references
References 37 publications
(54 reference statements)
1
159
1
2
Order By: Relevance
“…Unlike previous works that highlighted the important role exerted by a top coat layer for controlling the LC alignment by exploiting its polar-to-nonpolar chemical conversion [52], Fukuhara et al demonstrated that no additional coating procedure was necessary. The observed selective surface segregation of a surface-active polymer component could be exploited for applications requiring surface functions like adhesive and frictional properties and biocompatibility and for the fabrication of optical and mechanical devices based on LC alignment [53].…”
Section: Self-assembled Lcps Through Surface Effectsmentioning
confidence: 99%
“…Unlike previous works that highlighted the important role exerted by a top coat layer for controlling the LC alignment by exploiting its polar-to-nonpolar chemical conversion [52], Fukuhara et al demonstrated that no additional coating procedure was necessary. The observed selective surface segregation of a surface-active polymer component could be exploited for applications requiring surface functions like adhesive and frictional properties and biocompatibility and for the fabrication of optical and mechanical devices based on LC alignment [53].…”
Section: Self-assembled Lcps Through Surface Effectsmentioning
confidence: 99%
“…Fukuhara et al 128 showed that the photoresponsive skin layer of PBMA-b-PAz functions as a free-surface command layer for side chain LC polymer films containing a phenyl benzoate (PPBz) or cyanobiphenyl side chain (chemical structures shown in Figure 14). The procedures were the same as described for the PS-b-PAz.…”
Section: Command Surface Effect From the Free Surfacementioning
confidence: 99%
“…128 In this process, LPL was first used to irradiate an entire film area, followed by a subsequent irradiation with LPL in the orthogonal direction, as shown in Figure 16a. This procedures provided patterned in-plane alignment of the PPBz mesogens (Figure 16b).…”
Section: New Strategies In Photoalignment T Sekimentioning
confidence: 99%
“…For further functionalization of the LC polymer materials, molecular orientation, defect control and domain formation should be more precisely controlled. 269 For example, new techniques 44,[270][271][272][273] are proposed to control alignment using LC polymers. New materials will be used for the preparation of liquid crystals.…”
Section: Functional Lc Polymers and Networkmentioning
confidence: 99%